Performance and Emission Analysis of Motorcycles Using Pertalite-Methanol Fuel Blends - Lutanto, Agus; M. Burhan Rubai Wijaya; Hadromi (Multidisciplinary Innovations and Research in Applied Engineering, 2025)
The increasing use of motorcycles necessitates the development of more efficient and environmentally friendly fuel alternatives. This study examines the effect of mixing methanol with pertalite fuel on engine performance and exhaust emissions in carburetor motorcycles. The fuel variations tested include M0, M5, M10, M15, M20, and M25. Performance testing was conducted using a dynotest, while exhaust emissions were measured with an emission gas analyzer. The results indicate that M25 produces the highest torque and power output, particularly in the 2500–8500 rpm range. Additionally, M25 significantly reduces HC and CO emissions, with HC at 108.33 ppm vol and CO at 0.19% vol, compared to M0. The findings suggest that methanol-enhanced fuel improves combustion efficiency, enhances engine performance, and lowers emissions. Thus, methanol-pertalite blends offer a promising alternative for improving carburetor motorcycle performance while reducing environmental impact.